Consumers and Carer perspectives on poor practice and the use of seclusion and restraint in mental health settings: results from Australian focus groups. Issue 1 (December 2016) - Brophy, Lisa; Roper, Catherine; Hamilton, Bridget; Tellez, Juan; McSherry, Bernadette
Abstract Background Seclusion and restraint are interventions currently permitted for use in mental health services to control or manage a person's behaviour. In Australia, serious concerns about the use of such seclusion and restraint have been raised at least since 1993. Consumers and their supporters have also expressed strong views about the harm of these practices. This paper presents the results of ten focus group discussions with people with lived experience of mental health issues and also carers, family members and support persons in relation to the use of seclusion and restraint. Methods The 30 consumers and 36 supporters participating in the focus groups convened in four Australian cities and one regional centre discussed their understandings of the use of seclusion and restraint and its impact on the people involved. Participants also presented their observations about poor practice and what contributes to it as well as providing ideas and recommendations regarding strategies to reduce or eliminate seclusion and restraint. Focus group discussions were recorded and transcribed, then analysed using the NVivo 10 qualitative data analysis software with a general inductive approach used to analyse data. This analysis enabled consideration of the responses to key questions in the focus groups as well as the identification of emerging themes. Results Six themes emerged from the analysis, these being: human rights, trauma, control, isolation, dehumanisation and 'othering', and anti-recovery. Examples of poor practice identified by focus groups included the use of excessive force, lack of empathy/paternalistic attitudes, lack of communication and interaction and a lack of alternative strategies to the use of seclusion and restraint. There was a confluence of factors identified by participants as contributing to poor practice, with the main factors being organisational culture, the physical environment, under-resourced mental health services and fear and stigma. Conclusions Focus group participants in the main viewed seclusion and restraint practices in mental health settings as unnecessarily overused, exacerbating problems for individuals, carers, staff and the broader system of care. This study highlights that lived experience of both consumers and their supporters can make an important contribution to mental health services and its ongoing reform.